2018
DOI: 10.1159/000491768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Ticagrelor and Clopidogrel on Inflammatory Factors, Vascular Endothelium Functions and Short-Term Prognosis in Patients with Acute ST-Segment Elevation Myocardial Infarction Undergoing Emergency Percutaneous Coronary Intervention: a Pilot Study

Abstract: Background/Aims: Acute ST-segment elevation of myocardial infarction (STEMI) is the most severe type of acute coronary syndrome (ACS). Particular attention has been focused on studying the pathogenesis of STEMI, and how to prevent thrombosis, reduce inflammatory reaction, stabilize plaques and improve vascular endothelial functions to preserve the survived myocardium. This study aimed to compare the anti-inflammatory endothelium-protective effects, clinical prognosis, and relevant bleeding risks of ticagrelor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…In our previous study, we reported that ticagrelor decreased the occurrence rate of thrombosis, as well as ischemic outcome events, without causing any obvious increase in the risk of bleeding in acute STEMI patients receiving urgent percutaneous coronary intervention (PCI) [15]. In this study, we investigated the short-term efficacy (platelet inhibition) of ticagrelor and clopidogrel in acute ST-segment elevation myocardial infarction (STEMI) patients undergoing an emergency percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we reported that ticagrelor decreased the occurrence rate of thrombosis, as well as ischemic outcome events, without causing any obvious increase in the risk of bleeding in acute STEMI patients receiving urgent percutaneous coronary intervention (PCI) [15]. In this study, we investigated the short-term efficacy (platelet inhibition) of ticagrelor and clopidogrel in acute ST-segment elevation myocardial infarction (STEMI) patients undergoing an emergency percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…hs-CRP is considered as a risk factor of cardiovascular diseases and can increase the mortality of cardiovascular diseases 14,15 . CRP is involved in the pathogenesis and development of vascular in ammation and coronary atherosclerosis 16 .It directly affects complement activation, apoptosis, vascular cell activation, monocyte recruitment, lipid accumulation, and thrombosis and other atherosclerotic processes 17,18 . Epidemiological meta-analysis showed that hs-CRP > 3.0 mg/dL compared to < 1.0 mg/dL increased the risk of CAD by 1.6 times, and the hs-CRP levels were positively associated with the severity of coronary heart disease, which increase with the increase of lesion count 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cellspecific molecule 1 (ESM-1), also known as endocan, is a biomarker for endothelial dysfunction [103] and may serve as a novel evaluation method for risk stratification of patients with acute STEMI [104]. Another study also demonstrated that high endocan level at presentation was an independent predictor for adverse cardiac events [105,106].…”
Section: Endothelial Cell Related Biomarkersmentioning
confidence: 99%